1958
DOI: 10.1002/qj.49708436104
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐nucleating properties of some natural mineral dusts

Abstract: SUMMARYA fairly wide range of 28 naturally-occurring mineral dusts has been tested for ability to act as ice nuclei. 19 substances, mainly silicate minerals of the clay and mica groups, are found to be effective at -18°C; seven of these are active above -10°C. The most abundant of these is kaolinite with a threshold temperature of -9°C. 10 of the 28 substances, again mainly silicates, are found to become more efficient ice nuclei having once been involved in ice-crystal formation, i.e. they can be pre-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 13 publications
8
65
0
Order By: Relevance
“…Several earlier studies (Mason and Maybank, 1958;Roberts and Hallett, 1968;Shaller and Fukuta, 1979;Bailey and Hallett, 2002) demonstrated that the threshold temperature for ice nucleation by deposition freezing on kaolinite is about 253 K. For immersion mode freezing, an onset temperature of 259 K has been reported (Pitter and Pruppacher, 1973). The results presented here confirm that contact freezing is the most efficient ice nucleation process involving kaolinite particles, with freezing temperatures being observed up to 267 K. In previous work Pitter and Pruppacher (1973) studied contact freezing of water drops with kaolinite and montmorillonite particles.…”
Section: Discussionsupporting
confidence: 77%
“…Several earlier studies (Mason and Maybank, 1958;Roberts and Hallett, 1968;Shaller and Fukuta, 1979;Bailey and Hallett, 2002) demonstrated that the threshold temperature for ice nucleation by deposition freezing on kaolinite is about 253 K. For immersion mode freezing, an onset temperature of 259 K has been reported (Pitter and Pruppacher, 1973). The results presented here confirm that contact freezing is the most efficient ice nucleation process involving kaolinite particles, with freezing temperatures being observed up to 267 K. In previous work Pitter and Pruppacher (1973) studied contact freezing of water drops with kaolinite and montmorillonite particles.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, older reports have investigated the IN properties of pure feldspar samples in unknown modes (Isono and Ikebe, 1960;Mason and Maybank, 1958). In one study a cold chamber was used to report that 72.4 % of 40-60 µm soil particles containing 5 % feldspar nucleate ice in the immersion mode at temperatures below −20 • C (Rosinski and Nagamoto, 1976b).…”
Section: In Properties Of Feldspar Mineralsmentioning
confidence: 99%
“…Mineral dusts (particularly clay minerals) have been shown to be effective ice nucleating particles (INPs) [21][22][23][24][25][26], but determining precisely how composition and mineralogy affect ice nucleation activity (INA) is still up for debate. One study [27] investigated nine abundant minerals (quartz, albite, microcline, calcite, gypsum, montmorillonite, hematite, illite, and kaolinite) commonly found in mineral dust [28] and concluded that kaolinite, illite, and hematite were the most efficient INPs in the depositional mode.…”
Section: Introductionmentioning
confidence: 99%